A paleomagnetic analysis of the Patagonian Orocline - Rapalini, Augusto Ernesto (2007)
The dramatic change in the structural trend of the Andean orogen in southernmost Patagonia has long been considered a possible example of a true orocline. Paleomagnetism has proved a powerful tool to determine whether a curved orogen acquired its shape as a secondary feature. Paleomagnetic data obtained so far in the southern Patagonian and Fuegian Andes are reviewed in order to test the origin of the Patagonian orocline. Systematic counterclockwise (ccw) rotations along the arc are suggested by widespread ccw deflections of paleomagnetic declinations, which may be compatible with some secondary curvature of the orogen. Larger values of declination anomalies in the outer arc are consistent with some oroclinal bending related to mid-Cretaceous closure of the Late Jurassic – Early Cretaceous Rocas Verdes marginal basin. However, a thorough paleomagnetic test of the origin of the Patagonian Orocline is hampered by several problems that affect most results. These include scarce and unevenly distributed studied localities, low quality paleomagnetic data, lack of paleohorizontal control and uncertainty in magnetization ages. The fact that most data obtained so far is still scarce and questionable precludes a reliable answer to whether the southern Patagonian Fuegian Andes are a true orocline.